CHRONIC LOW BACK PAIN: IS THE MIND THE MISSING KEY TO QUALITY OF LIFE? A NARRATIVE REVIEW OF PSYCHOLOGICAL DETERMINANTS OF HEALTH-RELATED QUALITY OF LIFE - Natalia Rosół,; Natalia Kruszewska,; Natalia Ziółkowska,; Michał Cholewiński,; Paweł Szajewski,; Alicja Pełszyk,; Agata Pluta,; Justyna Kącikowska,; Daria Marciniak,; Justyna Łapicka, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and aim: Chronic low back pain (CLBP) is a highly prevalent musculoskeletal condition and a major contributor to disability worldwide. Its impact extends beyond physical symptoms, affecting emotional well-being, daily functioning and overall health-related quality of life (HRQoL). Increasing evidence suggests that psychological factors play a central role in shaping outcomes in CLBP. This narrative review summarises and critically discusses recent evidence (2022-2025) on the relationship between psychological factors and HRQoL in adults with CLBP, with particular emphasis on depression, anxiety, pain catastrophizing, kinesiophobia and self-efficacy.Methodology: A literature search was conducted in PubMed, Web of Science, Scopus, Google Scholar and the Cochrane Library. Original studies evaluating psychological factors in relation to pain, disability or HRQoL in adults with CLBP were included. Thirteen studies met the inclusion criteria, including cross-sectional and longitudinal designs, randomised controlled trials, one mediation analysis and one systematic review.Results: CLBP was consistently associated with impaired HRQoL across physical, emotional and social domains. Older age and female sex were linked with greater disability and lower HRQoL. Depression and anxiety showed the strongest associations with reduced well-being and long-term functional decline. Pain catastrophizing was negatively associated with HRQoL and increased risk of symptom generalisation. Kinesiophobia was linked with functional deficits and mediated treatment-related improvements. Self-efficacy was associated with better psychological outcomes, although its responsiveness to intervention varied across studies.Conclusions: Psychological factors are key determinants of HRQoL in patients with CLBP. Integrating psychological assessment into multidisciplinary care may improve quality of life and long-term management.